Recognizing the Effective Components of Architecture on Child Education, Based on the Islamic approach: Preschool Educational Spaces - Mahsa Aghajan; Samaneh Emami koupaei (علوم تربیتی از دیدگاه اسلام)
The effect of the surrounding physical environment on the child, confirms the place and role of architecture in child education. This is despite the fact that little research has been done on the role and capabilities of physical environments in shaping children's behaviors and actions. The present research is based on the studies conducted on educational teachings of Muslim religious texts, to provide an explanation of physical components and effective solutions of architecture on children's education. The type of research data is qualitative, and the data has been collected in both library and field methods. In this regard, in the first step, the child's educational components, which the physical environment can respond to, were extracted through the qualitative content analysis of the studies. The investigation showed that love and affection, respect for children and self-esteem, play and variety of activities, children's freedom, interaction and social vitality, intellectual discipline, rational thinking and questioning, role modeling and knowing of religious rules are among the educational indicators of religious texts. In the second step, semi-structured interviews were conducted with the teachers of five kindergartens in Isfahan, in order to complete and consider the efficiency of the extracted components. Teachers were selected purposefully and the interviews continued until theoretical persuasion. Finally, in order to match the results with the children's opinion, they were asked to paint their ideal kindergarten. The findings of the research confirmed the importance of the role of the physical environment in responding to these educational components. In addition, it showed that paying attention to environmental components such as comfort and psychological security, spatial diversity and attractiveness, connection with nature, flexibility, group interactions and play, in the architectural space, can improve the educational ability of the environment for the child.